2015
DOI: 10.1159/000430157
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Attenuated TNF-α-Induced Apoptosis in H9c2 Cells: Role of Calpain and the p38-MAPK Pathway

Abstract: This is an Open Access article licensed under the terms of the Creative Commons AttributionNonCommercial 3.0 Unported license (CC BY-NC) (www.karger.com/OA-license), applicable to the online version of the article only. Distribution permitted for non-commercial purposes only. Key Words Acetylcholine • Muscarinic receptor • Calpain • Calpastatin • p38-MAPK • ApoptosisAbstract Background: Previous studies have shown that inflammation is associated with excessive activation of calpains. Acetylcholine (ACh) has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Animal experiments implied that TNF‐α suppressed progression to T1DM. Abundant studies demonstrated that TNF‐α could induce apoptosis in various cells, such as HELA cells (Rajmani et al, ), H9c2 cells (Zhao et al, ), and MIN6 cells (Z. H. Cao et al, ). Moreover, TNF‐α is investigated to involve in insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments implied that TNF‐α suppressed progression to T1DM. Abundant studies demonstrated that TNF‐α could induce apoptosis in various cells, such as HELA cells (Rajmani et al, ), H9c2 cells (Zhao et al, ), and MIN6 cells (Z. H. Cao et al, ). Moreover, TNF‐α is investigated to involve in insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In response to apoptotic stimuli, Bax localizes from the cytosol to the mitochondrial membrane and increases the permeability of the membrane, which leads to the release of cytochrome c from the mitochondria. This release of cytochrome c activates caspase‐9, and caspase‐9 in turn activates caspase‐3 and caspase‐7, which are responsible for degrading the cell from within . Previous studies have demonstrated that hyperglycemia in cardiomyocytes induces the overexpression and phosphorylation of p53, which is linked to the downregulation of Bcl‐2 and the upregulation of Bax, thus initiating intrinsic apoptotic pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of extracts on TNF-α-induced apoptosis. The effect of the four water extracts on the TNF-αinduced cardiomyocyte injury and cell death was determined by using method of 33 with modifications. Briefly, 1 × 10 5 cells were seeded into 96 well plates and exposed for 18 h to sera free medium as above after 24 h. The cardiomyocytes were induced with rat TNF-α (250 pg/mL) from the (TNF-α) ELISA kit (E-EL-R0019, Elabscience, Biocom Africa) for 2 h before treatment with extracts (25 and 50 µg/mL) and positive control quercetin (12.5 and 25 µg/mL) and incubated over 24 h. After 24 h mitochondrial activity was measured using Resazurin assay kit (AR002, R & D, Whitehead Scientific) according to the manufacture manual and viability of cells in percentages was calculated same as in "Mitochondrial activity" section.…”
Section: Treatment Of Cellsmentioning
confidence: 99%